The Influence of Socio-Economic and Psychological Factors on the Composition of Household Solid Waste in Farahzad Neighborhood, Tehran, Iran - Shaghayegh Gharagozloo; Mahdi Jalili Ghazizade (SAGE Publishing, 2023)
Appropriate solid waste management requires correct identification of its quantitative and qualitative characteristics. Permanent changes in household solid waste composition (especially in developing countries) necessitate identifying factors affecting the composition to avoid frequent, extensive and high-cost sampling. The case study here is Farahzad Neighborhood in Tehran, a region where solid waste is not collected and managed properly, in turn, threatening the health of the residents in that area. The current study aims to identify socio-economic and psychological factors affecting household waste composition in this region. The data collection tool was a questionnaire, completed from July to August 2020, where 66 households were randomly selected as representative of 1950 households. Different parametric statistical tests were undertaken using the SPSS software to characterize factors affecting the waste composition in the research area. The results showed a significant difference (sig < .05) in the amount of recyclables in terms number employed people and household members as well education levels. There was also a significant difference (sig < .05) between the amount of food waste and education level, yet no (sig > .05) between the knowledge of waste management and the amount of generated plastics. Overall, this information may benefit managers and decision-makers to set more effective and socially inclusive policies for storing, collecting, and disposing of solid waste to ensure people from lower socio-economic groups are considered as well.